Postirradiation Cognitive and CNS Disabilities - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The neurological, neuropsychological, and educational outcome in 14 children who received a second course of cranial radiotherapy or total body irradiation for relapsing lymphoblastic leukemia is reported from the Neurosciences Unit and Department of Haematology, Institute of Child Health, University of London.